Analisa Pemborosan Pada Proses Produksi Air Minum Dalam Kemasan Dengan Metode Value Stream Mapping Dan Waste Assesment Model Di CV Dafista Mulia - Moh Rizky Ainul Yakin; Enny Aryanny (Jurnal Kendali Teknik dan Sains, 2023)
CV Dafista Mulia is a drinking water producer company located in Lamongan Regency. The problem that is often faced by companies is the amount of waste that occurs in the process of producing bottled drinking water. The most critical percentage of waste in the bottled water production process (AMDK) is waste overproduction with a weighting percentage of 25.4%; waste defet with a weighting percentage of 16.2%; waste inventory with a weighting percentage of 14.9%; waste unnecessary motion with a weighting percentage of 14.1%; waste transportation with a weighting percentage of 11.7%; waste waiting with a weighting percentage of 9%; and waste excess processing with a weighting percentage of 8.7%. The initial activity time before the repair was 466 minutes (7 Hours 46 Minutes) and after the repair was reduced to 416 minutes (6 Hours 51 Minutes). Based on the Failure Mode and Effect Analysis (FMEA), it is known that the root cause of the problem with the highest waste is Overproduction, namely production planning that is not quite right with a Risk Priority Number (RPN) score of 396. Recommendations for improvements that can be proposed are to carry out production planning using data - historical data that exists and is adjusted to balance the purchasing of raw materials with orders from consumers so that the results of the Overproduction can become a safety stock so that the Overproduction can function in the next consumer order.